Structural elucidation of NASICON (Na3Al2P3O12) based glass electrolyte materials: effective influence of boron and gallium - Allu, Amarnath R. (RSC Advances, 2018)
Understanding the conductivity variations induced by compositional changes in sodium super ionic conducting (NASICON) glass materials is highly relevant for applications such as solid electrolytes for sodium (Na) ion batteries. In the research reported in this paper, NASICON-based NCAP glass (Na2.8Ca0.1Al2P3O12) was selected as the parent glass. The present study demonstrates the changes in the Na+ ion conductivity of NCAP bulk glass with the substitution of boron (NCABP: Na2.8Ca0.1Al2B0.5P2.7O12) and gallium (NCAGP: Na2.8Ca0.1Al2Ga0.5P2.7O12) for phosphorus and the resulting structural variations found in the glass network. For a detailed structural analysis of NCAP, NCABP and NCAGP glasses, micro-Raman and magic angle spinning-nuclear magnetic resonance (MAS-NMR) spectroscopic techniques (for 31P, 27Al, 23Na, 11B and 71Ga nuclei) were used. The Raman spectrum revealed that the NCAP glass structure is more analogous to the AlPO4 mesoporous glass structure. The 31P MAS-NMR spectrum illustrated that the NCAP glass structure consists of a high concentration of Q0 (3Al) units, followed by Q0 (2Al) units. The 27Al MAS-NMR spectrum indicates that alumina exists at five different sites, which include AlO4 units surrounded by AlO6 units, Al(OP)4, Al(OP)5, Al(OAl)6 and Al(OP)6, in the NCAP glass structure. The 31P, 27Al and 11B MAS-NMR spectra of the NCABP glass revealed the absence of B–O–Al linkages and the presence of B3–O–B4–O–P4 linkages which further leads to the formation of borate and borophosphate domains. The 71Ga MAS-NMR spectrum suggests that gallium cations in the NCAGP glass compete with the alumina cations and occupy four (GaO4), five (GaO5) and six (GaO6) coordinated sites. The Raman spectrum of NCAGP glass indicates that sodium cations have also been substituted by gallium cations in the NCAP glass structure. From impedance analysis, the dc conductivity of the NCAP glass (∼3.13 × 10−8 S cm−1) is slightly decreased with the substitution of gallium (∼2.27 × 10−8 S cm−1) but considerably decreased with the substitution of boron (∼1.46 × 10−8 S cm−1). The variation in the conductivity values are described based on the structural changes of NCAP glass with the substitution of gallium and boron.

Ionic conductivity of Na3Al2P3O12 glass electrolytes role of charge compensators - Keshri, Shweta R.; Ganisetti, Sudheer; Kumar, Rajesh; Gaddam, Anuraag; Illath, Kavya; Ajithkumar, Thalasseril G.; Balaji, Sathravada; Annapurna, K.; Nasani, Narendar; Krishnan, N. M. Anoop; Allu, Amarnath R. (Inorganic Chemistry, 2021)
In glasses, a sodium ion (Na+) is a significant mobile cation that takes up a dual role, that is, as a charge compensator and also as a network modifier. As a network modifier, Na+ cations modify the structural distributions and create nonbridging oxygens. As a charge compensator, Na+ cations provide imbalanced charge for oxygen that is linked between two network-forming tetrahedra. However, the factors controlling the mobility of Na+ ions in glasses, which in turn affects the ionic conductivity, remain unclear. In the current work, using high-fidelity experiments and atomistic simulations, we demonstrate that the ionic conductivity of the Na3Al2P3O12 (Si0) glass material is dependent not only on the concentration of Na+ charge carriers but also on the number of charge-compensated oxygens within its first coordination sphere. To investigate, we chose a series of glasses formulated by the substitution of Si for P in Si0 glass based on the hypothesis that Si substitution in the presence of Na+ cations increases the number of SiOAl bonds, which enhances the role of Na as a charge compensator. The structural and conductivity properties of bulk glass materials are evaluated by molecular dynamics (MD) simulations, magic angle spinning-nuclear magnetic resonance, Raman spectroscopy, and impedance spectroscopy. We observe that the increasing number of charge-imbalanced bridging oxygens (BOs) with the substitution of Si for P in Si0 glass enhances the ionic conductivity by an order of magnitudefrom 3.7 x 10(-8) S.cm(-1) to 3.3 x 10(7) S.cm(-1) at 100 degrees C. By rigorously quantifying the channel regions in the glass structure, using MD simulations, we demonstrate that the enhanced ionic conductivity can be attributed to the increased connectivity of Na-rich channels because of the increased charge-compensated BOs around the Na atoms. Overall, this study provides new insights for designing next-generation glass-based electrolytes with superior ionic conductivity for Na-ion batteries